A new tool to assess community-level evidence to inform public health decision making. (30th September 2020) - Clark, E; Snelling, S; Beyers, J; Howarth, C; Neil-Sztramko, S; Dobbins, M
Abstract: Background: As public health responds to evolving challenges around the globe, it is critical to draw on community-level evidence to inform decisions on emerging needs. There are existing tools for assessing the quality of research evidence, but none that explicitly focus on quality assessment of evidence from community sources, including local health status and ever-changing community and political preferences and actions. Methods: The National Collaborating Centre for Methods and Tools (NCCMT) in Canada has developed new tools, called Quality Assessment of Community Evidence (QACE), to help public health decision makers assess the quality of community evidence. The QACE tools were drafted through extensive review of existing frameworks, tools and measures for appraising population health and community evidence, and diverse key informants. We identified three consistent themes that became the core dimensions in these tools. By using the QACE tools, practitioners can answer the question: "Is the quality of this evidence about local context, community needs and political preferences good enough to influence decision making?" Results: The QACE tools provide probing questions for each of three dimensions: relevant, trustworthy and equity-informed. Supplementary resources help users delve more deeply into different aspects of quality assessment. The QACE tools are intended for public health practitioners who provide and use evidence to support or make decisions about public health practice and policy, including public health practitioners, senior leaders, policy makers and funders. Conclusions: The QACE tool is a new addition to the public health toolbox for evidence-informed decision making, providing questions to ask about evidence from community sources. By using the tool as part of a decision-making process, public health practitioners can be assured that their decisions are based on the best-available evidence for their communities. Key messages: The new Quality Assessment of Community Evidence (QACE) tools fill the gap in assessing quality of community-level evidence for public health decision-makers. Community evidence, including local health status and needs and community and political preferences and actions, should be assessed for quality in three critical domains.